Potential relationship between Tourette syndrome and gut microbiome - Junze Geng; Can Liu; Jingyu Xu; Xiaoge Wang; Xinmin Li (Elsevier, 2023)
Objective: In this article, the author aims to discuss and review the relationship between gut microbiota and Tourette syndrome, and whether the change in gut microbiota can affect the severity of Tourette syndrome. Sources: Literature from PubMed, Google Scholar, and China National Knowledge Infrastructure was mainly reviewed. Both original studies and review articles were discussed. The articles were required to be published as of May 2022. Summary of the findings: Current studies on the gut microbiome have found that the gut microbiome and brain seem to interact. It is named the brain-gut-axis. The relationship between the brain-gut axis and neurological and psychiatric disorders has been a topic of intense interest. Tourette syndrome is a chronic neurological disease that seriously affects the quality of life of children, and there appears to be an increase in Ruminococcaceae and Bacteroides in the gut of patients with Tourette syndrome. After clinical observation and animal experiments, there appear to be particular gut microbiota changes in Tourette syndrome. It provides a new possible idea for the treatment of Tourette syndrome. Probiotics and fecal microbial transplantation have been tried to treat Tourette syndrome, especially Tourette syndrome which is not sensitive to drugs, and some results have been achieved. Conclusions: The relationship between gut microbiota and Tourette syndrome and how to alleviate Tourette syndrome by improving gut microbiota are new topics, more in-depth and larger sample size research is still needed.